2010
DOI: 10.1051/0004-6361/201015608
|View full text |Cite
|
Sign up to set email alerts
|

The missing gas problem in GRB host galaxies: evidence for a highly ionised component

Abstract: There is considerable discrepancy between the amount of X-ray absorption and what is inferred from optical (rest frame UV) as measured along gamma-ray burst (GRB) sight lines, with the former typically an order of magnitude higher than what would be expected from the measurement of neutral element species via optical absorption line spectroscopy. We explored this "missing gas problem" in a sample of 29 GRBs with redshifts in the range 0.7-6.3 by studying the X-ray and optical spectra, as well as the afterglow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 92 publications
3
89
0
Order By: Relevance
“…Campana et al 2009.) This would indeed be solved by the make-up of the dust being different, but this is hard to explain given the well-determined extinction laws that are observed in GRB afterglows, which are consistent with the Local Group extinction laws (Schady et al 2011;Greiner et al 2011;Covino et al 2013). One could argue that the problem arises from using a MW scaling relation with A V;SED measurements based upon mostly SMC-like extinction laws, but both Magellanic Clouds have similar a A V /N H to that in the MW (Zafar & Watson 2013;Watson 2011).…”
Section: Equivalent Dust Column Densitymentioning
confidence: 99%
“…Campana et al 2009.) This would indeed be solved by the make-up of the dust being different, but this is hard to explain given the well-determined extinction laws that are observed in GRB afterglows, which are consistent with the Local Group extinction laws (Schady et al 2011;Greiner et al 2011;Covino et al 2013). One could argue that the problem arises from using a MW scaling relation with A V;SED measurements based upon mostly SMC-like extinction laws, but both Magellanic Clouds have similar a A V /N H to that in the MW (Zafar & Watson 2013;Watson 2011).…”
Section: Equivalent Dust Column Densitymentioning
confidence: 99%
“…A number of previous studies have already revealed some clues about the geometry of the absorbing matter, which have been derived quite exclusively from sight-lines of low total dust content: the distance of the cold-neutral material, linked to the DLA and the low-ionization metal absorption lines has been constrained to be between a few hundreds of pc and a few kpc (Prochaska et al 2006;Vreeswijk et al 2007). In contrast, the high metal column densities as derived from soft X-ray absorption were associated with a fully ionized circumburst medium up to a few to several tens of pc (Watson et al 2007;Schady et al 2011a). For bursts with largely unextinguished afterglows, most of the metals along the sight-line are typically in a highly ionized state and only 10% of the absorbing gas is neutral (Schady et al 2011a).…”
Section: Location and Geometry Of The Absorbing Dust Columnmentioning
confidence: 99%
“…Prochaska et al 2007a;D'Elia et al 2011;Schady et al 2011;Sparre et al 2014;Friis et al 2015;Wiseman et al 2017), there is much less known about the systems hosting GRBs with a much lower hydrogen column density. Typically, they are left out of studies based on metals and dust due to the complicated effects of ionisation, which at higher column densities is rendered negligible (Viegas 1995;Wolfe et al 2005;Peroux et al 2007).…”
Section: Introductionmentioning
confidence: 99%